Impact of five floor coverings on the orthostatic balance of healthy subjects - Bonardet, Nathalie; Chapus, Jean; Lefaucheur, Jean-Pascal; Lampire, Nicolas; Créange, Alain; Sorel, Marc (Experimental brain research, 2023)
Plantar skin sensitivity contributes to the regulation of postural control and, therefore, changing the characteristics of the plantar support surface can modify this control. This study aimed at assessing the impact of five different floor coverings on the orthostatic balance in 48 healthy subjects. Static posturography was performed with eyes open or closed on a platform in a control condition (no covering) and with five different covering surfaces: foam, silicone, ethyl vinyl acetate, and two textured mats with small (height 2 mm) or large pimples (7 mm). The average velocity of center of pressure (CoP) displacement was the primary endpoint measure and ten other posturographic variables were assessed. Comfort and pain produced by the covering were also scored. In eyes open condition, the average velocity of CoP displacement was increased when subjects stood on the foam mat, the silicone mat, and especially the textured mat with large pimples. Several other posturographic variables showed significant changes with different types of floor coverings with eyes open. These changes were not correlated to the comfort or pain scores associated with the different surfaces. In contrast, no difference was observed compared to the control condition (no covering) with eyes closed. This study shows that adding smooth or textured floor covering can alter balance in eyes open condition. In eyes closed condition, although more disturbing for balance, healthy subjects achieved better postural adaptation, probably by mobilizing more of their proprioceptive resources. This posturographic examination procedure could, therefore, be used to assess “proprioceptive reserve” capacities in clinical practice.